2016
DOI: 10.3389/fnint.2016.00034
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Activity in the Human Frontal and Parietal Cortex Differentiate Large and Small Saccades

Abstract: A vast literature indicates that small and large saccades, respectively, subserve different perceptual and cognitive strategies and may rely on different programming modes. While it is well-established that in monkeys’ main oculomotor brain regions small and large eye movements are controlled by segregated neuronal populations, the representation of saccade amplitude in the human brain remains unclear. To address this question we used functional magnetic resonance imaging to scan participants while they perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
(98 reference statements)
1
3
0
Order By: Relevance
“…1 and Table 3 ). Our results thus suggest a robust association of structure and function in these higher PFC regions (Frost and Goebel 2012 ; Miller et al 2021 ; Van Essen 2007 ; Wang et al 2015 ), analogous to what previous studies have shown in early visual regions (Benson et al 2012 ; Hinds et al 2008 ). We suggest that this association should be examined by future fMRI studies more systematically at the individual-subject level (Amiez et al 2006 ; Amiez and Petrides 2018 ; Derrfuss et al 2009 , 2012 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1 and Table 3 ). Our results thus suggest a robust association of structure and function in these higher PFC regions (Frost and Goebel 2012 ; Miller et al 2021 ; Van Essen 2007 ; Wang et al 2015 ), analogous to what previous studies have shown in early visual regions (Benson et al 2012 ; Hinds et al 2008 ). We suggest that this association should be examined by future fMRI studies more systematically at the individual-subject level (Amiez et al 2006 ; Amiez and Petrides 2018 ; Derrfuss et al 2009 , 2012 ).…”
Section: Discussionsupporting
confidence: 87%
“…That such a link can in principle be successfully accomplished has been demonstrated in the visual system, where studies have shown that despite the inter-individual variability in the surface area of the early visual cortex (Benson et al 2022 ), specific anatomical landmarks (i.e., sulci) coincide very well with the borders of early visual areas as derived from various sources of data, including cytoarchitecture, retinotopic mapping, myelin content and resting-state fMRI functional connectivity (Abdollahi et al 2014 ; Fischl et al 2008 ; Glasser et al 2016 ; Sereno et al 1995). Hinds et al ( 2008 ) used surface-based registration methods (Fischl et al 1999 ) to identify V1 in new subjects from cortical folding information (i.e., the stria of Gennari) and showed that these methods outperformed volumetric methods in labeling this structure. Similarly, Benson et al ( 2012 ) used folding information to predict visual responses within the striate cortex to a retinotopic mapping fMRI protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Are these populations of neurons also present in humans, and how are they distributed within the FEF? Are these neurons associated with the significant increase in the BOLD signal when comparing saccades to peripheral positions against a fixation baseline, and what is the role of saccadic amplitude in isolating peaks of activity within the FEF (see Grosbras 2016)? An additional aspect that may be worth investigating is whether the activations found in one or more of these clusters (for example, the iFEF) are dependent on some artifacts present in the experimental design or analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cortical regions modulated by across-hemifield remapping showed no (or very little) overlap with cortical regions that were activated during saccadic execution, but consistently were located in slightly more anterior, abutting portions of parietal cortex. It is unlikely that these differences reflect different eccentricities of the to-be-remembered dots and saccade targets, because it has been shown that even much larger eccentricity differences (4° vs 30°) do not result in any univariate BOLD differences in parietal cortex (Grosbras, 2016). Furthermore, although we were unable to separate saccade localizer trials based on saccade direction, the bilateral remapping activation observed was distinct from the combined ocular motor activation from right and left saccades, which would not be expected to differ spatially if right and left saccades were analyzed separately.…”
Section: Parietal Activations For Spatial Attention Visual Remapping and Motor Generationmentioning
confidence: 99%